The Role of IL-17 in Papulopustular Rosacea and Future Directions. Issue 6 (November 2019) - Amir Ali, Asma; Vender, Reid; Vender, Ronald
Rosacea is a chronic, progressive, inflammatory condition phenotypically subtyped into diagnostic features, major features, and minor/secondary features. There is currently no cure for rosacea, and it carries a significant negative psychosocial burden for afflicted patients. While there are a number of treatment modalities at the disposal of the clinician, clinical experience has suggested a need for updated treatments. The pathogenesis of rosacea is multifactorial; however, this paper will focus on the pivotal role of interleukin 17 (IL-17) in the development and progression of the disease. Furthermore, this paper will explore the mechanism of action of standard rosacea treatments and their effect on different stages of the IL-17 pathway. The standard treatments for rosacea are usually effective in controlling the symptoms of the disease in its mild-to-moderate form; however, their efficacy is diminished in the setting of severe and treatment-resistant rosacea. We hypothesize that IL-17 inhibitors, currently used successfully in psoriasis and psoriatic arthritis, could perhaps be used to treat severe and treatment-resistant papulopustular rosacea in the future; however, clinical trials and case reports will be needed to dictate expanded indications of IL-17 inhibitors. Furthermore, the high cost of IL-17 inhibitors presently prevents their use in disease states other than psoriasis or psoriatic arthritis.